Interferon and Hepatitis B: Current and Future Perspectives - Ye, Jianyu; Chen, Jieliang (Frontiers in Immunology, 2021)
Chronic hepatitis B virus (HBV) infection remains a major health burden worldwide for which there is still no effective curative treatment. Interferon (IFN) consists of a group of cytokines with antiviral activity and immunoregulatory and antitumor effects, that play crucial roles in both innate and adaptive immune responses. IFN-α and its pegylated form have been used for over thirty years to treat chronic hepatitis B (CHB) with advantages of finite treatment duration and sustained virologic response, however, the efficacy is limited and side effects are common. Here, we summarize the status and unique advantages of IFN therapy against CHB, review the mechanisms of IFN-α action and factors affecting IFN response, and discuss the possible improvement of IFN-based therapy and the rationale of combinations with other antiviral agents in seeking an HBV cure.